Materializing difference : consumer culture, politics, and ethnicity among Romanian Roma - Berta, Péter, 1972- (Anthropological horizons., 2019)
"How do objects mediate human relationships, and possess their own social and political agency? What role does material culture--such as prestige consumption as well as commodity aesthetics, biographies, and ownership histories--play in the production of social and political identities, differences, and hierarchies? How do (informal) consumer subcultures of collectors organize and manage themselves? Drawing on theories from anthropology and sociology, specifically material culture, consumption, museum, ethnicity, and post-socialist studies, Materializing Difference addresses these questions via analysis of the practices and ideologies connected to Gabor Roma beakers and roofed tankards made of antique silver. The consumer subculture organized around these objects--defined as ethnicized and gendered prestige goods by the Gabor Roma living in Romania--is a contemporary, second-hand culture based on patina-oriented consumption. Materializing Difference reveals the inner dynamics of the complex relationships and interactions between objects (silver beakers and roofed tankards) and subjects (Romanian Roma) and investigates how these relationships and interactions contribute to the construction, materialization, and reformulation of social, economic, and political identities, boundaries, and differences. It also discusses how, after 1989, the political transformation in Romania led to the emergence of a new, post-socialist consumer sensitivity among the Gabor Roma, and how this sensitivity reshaped the pre-regime-change patterns, meanings, and value preferences of prestige consumption."--